Anesthetic Implications of Nephrotic Syndrome in Neurosurgical Practice - Puthiyedath, Roshna C.; Kumar, Ashutosh; Praveen, Ranganatha; Sethuraman, Manikandan (Journal of Neuroanaesthesiology and Critical Care, 2022)
Nephrotic syndrome (NS) is a common medical disorder especially in pediatric population with hypoproteinemia as an important feature. NS has multisystem involvement and multiple organ effects due to the disease or the treatment itself, which has important implications in the perioperative period. Hypoproteinemia in NS can result in reduction in availability of protein binding sites for certain intravenous anesthetics, leading to their increased free fraction that can concentrate at the receptor sites, thereby prolonging their action. NS can have phases of relapse and remission with increased propensity for complications, such as thromboembolism during relapse phase. Such patients presenting for neurosurgery pose unique challenge to the anesthesiologist. We hereby report a case of NS and its implication in neurosurgical practice and management.
Keywords: nephrotic syndrome; steroid resistant; idiopathic intracranial hypertension; proteinuria